Huntress - Lo, Malinda (Little, Brown, 2011)
Seventeen-year-olds Kaede and Taisin are called to go on a dangerous and unprecedented journey to Tanlili, the city of the Fairy Queen, in an effort to restore the balance of nature in the human world.